The Impact of Heterogeneity on Single-Cell Sequencing - Goldman, Samantha L.; MacKay, Matthew; Afshinnekoo, Ebrahim; Melnick, Ari M.; Wu, Shuxiu; Mason, Christopher E. (Frontiers in Genetics, 2019)
The importance of diversity and specialization is clear for many reasons, from population-level diversification to improve resiliency to unforeseen stresses to specialization within multicellular organisms from development and differentiation. However, the level of cellular heterogeneity is just now becoming clear through the integration of genome-wide analyses such as Next Generation Sequencing. With the rise of single-cell NGS (scNGS) we are now capable of witnessing how diverse cells are at different levels of gene expression and somatic mutational heterogeneity. In this perspective we discuss the importance of understanding heterogeneity and the application of NGS, with a focus on the utilization of single cell next generation sequencing and a guide to aid in sample size and experimentation design.